PROFITABILITAS BANK PEMBANGUNAN DAERAH NON GO PUBLIC DI INDONESIA - Rosalina, Made Kiki; Suartana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024, 2024)
The aim of the study is to determine the effect of credit risk, level of lending, and operational risk on profitability at non go public regional development banks in Indonesia year 2019-2021. This study uses a sample of 63 non go public regional development banks and data analysis techniques that multiple linier regression with first performed classical assumption. The result of the study found that variable credit risk has no significant negative effect on profitability, variable level of lending has a significant positive effect on profitability, and variable operational risk has a significant negative effect on profitability. This research makes a positive contribution to all parties, especially BPD management in improving performance and maximizing the factors that affect profitability so that BPD can still develop. This research also makes a positive contribution to the reading community, namely as additional knowledge in making decisions to use certain bank service, whether saving or borrowing funds based on bank performance.